A novel STAT1 loss-of-function mutation associated with Mendelian susceptibility to mycobacterial disease - Ye, Fanghua; Zhang, Wen; Dong, Jiajia; Peng, Min; Fan, Chenying; Deng, Wenjun; Zhang, Hui; Yang, Liangchun (Frontiers in Cellular and Infection Microbiology, 2022)
Mendelian susceptibility to mycobacterial diseases (MSMD) is a rare congenital immune deficiency characterized by susceptibility to weakly virulent mycobacteria. Loss-of-function (LOF) mutation of signal transducer and activator of transcription 1 (STAT1) is one of the common genetic causes of MSMD. In this study, we identified a patient who presented with multiple lymph node enlargements and multiple osteolytic disruptions. Mycobacterium gordonae infection was confirmed by metagenomic next-generation sequencing. Whole-exome sequencing identified a novel paternal heterozygous mutation in exon 22 of STAT1 (NM_007315.4, c.1892T>C, p.Val631Ala). This variant was confirmed pathogenic by multiple software predictions. Based on functional assays, STAT1 expression in STAT1V631A cells was not different from STAT1WT cells. But STAT1V631A mutation caused much lower activation of STAT1 when stimulated by interferon-γ (IFN-γ). Fluorescence localization analysis revealed that both STAT1V631A and STAT1WT proteins were located in the cytoplasm, and only a few STAT1V631A proteins were translocated to the nucleus in response to IFN-γ. These results suggest that STAT1V631A leads to LOF in IFN-γ-mediated mycobacterial immunity, resulting in MSMD. Treatment with antibiotics has achieved ideal disease control for this patient, and no adverse events occurred during follow-up. The STAT1 LOF deficiency is a genetic cause of MSMD, which should be considered in patients with mycobacterial disease, especially those with bone involvement.